Zr‐Based Metal‐Organic Framework Films Grown on Bio‐Template for Photoelectrocatalysis. Issue 44 (23rd November 2020) - Sun, Shujian; Xiao, Yali; He, Lanqi; Tong, Yexiang; Liu, Dingxin; Zhang, Jianyong
Abstract: A series of Zr‐based metal‐organic framework (Zr‐MOF) films are anchored on the surface of butterfly wing via solvothermal method for HER application, including UiO‐66, NH2 ‐UiO‐66 and UiO‐67. Oriented nanoparticles are anchored on the photonic crystal bio‐template. The distinctive design of the Zr‐MOFs/B composites enables remarkable photoelectrocatalytic HER activity in comparison with corresponding intrinsic Zr‐MOFs, primarily due to the synergy effect between MOFs and the photonic crystal. The cathode current increases to 1.94, 0.98 and 3.64 mA cm −2 for UiO‐66/B, NH2 ‐UiO‐66/B and UiO‐67/B, respectively, at an overpotential of −0.6 V vs RHE when irradiated for 30 min upon simulated sunlight. Upon simulated sunlight irradiation, the carrier density increases by 2.00, 1.26 and 1.48 times for UiO‐66/B, NH2 ‐UiO‐66/B and UiO‐67/B, respectively. This work paves a promising pathway for designing efficient HER electrocatalysts by combination of Zr‐MOFs and photo‐active butterfly wings. Abstract : A series of Zr‐based metal‐organic framework nanoparticles are deposited on the surface of butterfly wing via solvothermal method for photoelectrocatalytic HER application.